LITERATUR REVIEW : IMPLEMENTATION OF TARGET COSTING IN MSMEs - Nur Israq Fauziah; Aristanti Widyaningsih; Denny Andriana (Yayasan Nuraini Ibrahim Mandiri, 2024)
The process of determining the highest costs that can be incurred during the manufacture of a new product is known as target costing. Within the constraints of a given maximum cost, a profitable prototype is then designed. Target costing is a method that is suitable for use by Micro, Small and Medium Enterprises in Indonesia to increase profits. The research method uses a literature review using 32 relevant articles. Of the 32 articles, several articles stated that the company had implemented predetermined costing targets. One of the articles that has implemented target costing is Gunung Seulawah MSMEs in the food sector, which shows that the company can optimize profits well and achieve profits of more than 25% compared to other MSMEs. Many studies have helped implement target costing in several MSMEs from various different sectors, which it is hoped will help the community to implement it so that it can increase profits to help the progress of MSMEs.